60th ANNIVERSARY OF THE BUDKER INSTITUTE OF NUCLEAR PHYSICS (BINP), SB RAS. 100th ANNIVERSARY OF THE BIRTH OF G I BUDKER : Free electron lasers and their development at the Budker Institute of Nuclear Physics, SB RAS. (8th August 2018) - Vinokurov, N A; Shevchenko, O A
Abstract: This review is devoted to free electron lasers (FELs) and their development research at the Budker Institute of Nuclear Physics (INP), SB RAS. Basic principles of FEL physics are considered. Selected studies from forty years of research are presented. The unique Novosibirsk FEL research facility is briefly described.